Harnessing the benefits of available targeted therapies in acute myeloid leukaemia. Issue 12 (December 2021) - Kantarjian, Hagop; Short, Nicholas J; DiNardo, Courtney; Stein, Eytan M; Daver, Naval; Perl, Alexander E; Wang, Eunice S; Wei, Andrew; Tallman, Martin
Summary: Research has resulted in regulatory approval of nine agents for acute myeloid leukaemia indications by the US Food and Drug Administration since 2017: the Bcl-2 inhibitor, venetoclax; two FLT3 inhibitors, midostaurin and gilteritinib; two IDH inhibitors, ivosidenib (IDH1 inhibitor) and enasidenib (IDH2 inhibitor); the anti-CD33 antibody–drug conjugate, gemtuzumab ozogamicin; the oral, poorly absorbable hypomethylating agent, azacitidine; the liposomal formulation of cytarabine and daunorubicin (5:1 ratio), CPX-351; and the hedgehog signalling pathway inhibitor, glasdegib. A 100% absorbable oral formulation of the hypomethylating agent decitabine was approved for the treatment of myelodysplastic syndrome and chronic myelomonocytic leukaemia, and might be used as an alternative to parenteral hypomethylating agents. Several of the approvals are as single-agent therapies or in specific combinations for narrow indications, thus offering poor treatment value. In this Review, we discuss ongoing research into combinations containing these commercially available targeted therapies for acute myeloid leukaemia.